(untitled) (Philological Studies, 2019)
The Bogomil movement in its authentic form appeared in the South-Western parts of Macedonia in the middle of 10th century. The main preacher and ideological creator was the priest Bogomil, whose initial activity is chronologically connected to the 30’s of 10th century. The idea of Bogomilsm as an authentic spiritual manifestation was probably due to his theoretical experiences and objective judgment, but the integral realization of this ideology with theological, dualistic, philosophical and cultural indications represents the result of many-years collective work with the closest associates and sympathizers. Priest Bogomil’s pragmatism lies mainly in his ability to coordinate his followers for a complete realization of Bogomilism as a movement and as a teaching. The existing of Bogomilsm in Macedonia took place until 15th century, and at the same time it was periodically adapting its concept of action depending on the current social, political, religious and ideological circumstances. The religious and dualistic concept of Bogomilsm also had an evident influence on the cultural and spiritual processes and tendencies in Macedonia and wider on the Balkans, Byzantium and in some way in the countries of Western Europe. The cultural aspects of the movement could be identified through the literary tradition (literary works with original Bogomil status and apocryphal texts), than philosophical tendencies and finally through the authentic folk heritage with dualistic character.